Optimizing Digital Platform Marketing Strategies: Analysis of Impuls Purchase Behavior in Live Streaming Commerce on Gen Z In Pekanbaru, Indonesia - Diana Eravia; Qomariah Lahamid; Zulhaida Zulhaida; Qonitah Rifda Zahirah (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to analyze the effectiveness of live streaming commerce marketing strategies in encouraging spontaneous purchases among Generation Z in Pekanbaru, Indonesia. Using a quantitative approach through Structural Equation Modeling (SEM)-PLS on 124 respondents, the study tested the influence of real-time interactivity, host credibility, and entertainment atmosphere on impulsive purchase intent through customer engagement as a mediating variable. The results revealed that host credibility significantly affected customer engagement (Î² = 0.294, p = 0.021), while real-time interactivity and entertainment atmosphere showed no significant direct influence. Customer engagement showed a strong positive influence on impulse purchase intent (Î² = 0.758, p = 0.000) and mediated a full relationship between host credibility and impulse purchase. This model explains a 56.6% variation in impulsive buying intent (RÂ² adjusted = 0.566). These findings suggest that a successful live streaming commerce strategy should prioritize building host credibility and increasing customer engagement over just entertainment features or interactive functionality. The research provides practical implications for digital marketers to optimize their live streaming commerce strategies with a focus on developing authentic hosts and meaningful customer engagement initiatives, particularly in targeting the Gen Z demographic in emerging markets like Indonesia. Keywords: Digital Marketing, Live Streaming Commerce, Impulse Purchases, Customer Engagement, Host Credibility, Generation Z